The Effect of Influencer Marketing, Live Streaming, Brand Awareness and Price on Purchasing Decisions for TikTok Users - Dewi, Nyoman Ayu Nidya Larasati; Maradona, Agus Fredy (Quantitative Economics and Management Studies, 2024)
This study aims to explore the role of influencer marketing and live streaming on the TikTok platform in promoting products and their relationship to consumer brand awareness, pricing, and purchasing decisions. Conducted using a quantitative approach in the province of Bali, the target population included all consumers aged 17-50 who use the TikTok app. Through sampling methods, 204 TikTok users in Bali participated in the study. Empirical data was collected via online questionnaires using a 10-point Likert scale and analyzed using SEM-PLS approach. The study findings identify that influencer marketing and live streaming significantly influence purchasing decisions, both directly and through Brand Awareness and Price as strong intervening constructs. The results underscore the importance of influencer capabilities and the quality of live streaming content in enhancing brand awareness, pricing perceptions, and increasing consumer desire to purchase products. This research provides both theoretical and practical contributions for developing digital marketing strategies, particularly in effectively leveraging TikTok as a social media platform to enhance consumer purchasing decisions.